A Study of the Factors Affecting Universiti Tun Hussein Onn Malaysia Students’ Entrepreneurial Intention - Mohammed Abdullah, Abdulhameed Mohammed; Omar, Siti Sarah; Al-Shameri, Ahmed Saleh Ahmed Saif; Abdullah Abkar, Mahdi Mohmmed (Journal of Techno-Social, 2023)
Unemployment is an issue in most of the countries, both developing and developed. Students spend their available life, money, and efforts in education for getting a good job. However, when they finish their education, they spend much time looking for a job and sometimes stay unemployed. It is believed that one of the best solutions for this problem is to start a privet business. Thus, this study embarked to study the factors that affect UTHM students’ entrepreneur intention. It followed the quantitative method and collected the data via online and hard questionnaires. The data then was analyzed using the Statistical Package for Social Science (SPSS) version 22.0. Four main variables were studied in this research namely, attitude, perceived behavior control, need for achievement, and family background. The findings of this study showed that all the variables were correlated with entrepreneurial intention. Moreover, the study also showed that all factors have a significant impact on entrepreneurial intention, except for the family background which was found to have no significant impact.